2019
DOI: 10.1093/eurheartj/suz075
|View full text |Cite
|
Sign up to set email alerts
|

Results of the May Measurement Month 2017: blood pressure campaign in Venezuela—Americas

Abstract: Cardiovascular diseases, mainly coronary heart disease and stroke, are the first cause of death in Venezuela; and hypertension is the main risk factor. May Measurement Month (MMM) is a global initiative aimed at raising awareness of elevated blood pressure (BP) and to act as a temporary solution to the lack of regular screening programmes. Some representative studies indicate prevalence of hypertension in Venezuela between 24 and 39%, and control rate around 20%. Sixty-four sites were included to participate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In MMM21 in Venezuela, the percentage of participants with hypertension was 60.3%, which is higher than in previous MMM studies for Venezuela. 5–7 For example, in 2019, 48.9% were classified as hypertensive, 6 which may be due in small part to an older average age of 2021 screenees (56.4 vs. 54.7 years). On the other hand, sampling of MMM campaigns is opportunistic and not randomized, and it is possible that hypertensive patients participated in higher numbers than in previous years after the restrictions from the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In MMM21 in Venezuela, the percentage of participants with hypertension was 60.3%, which is higher than in previous MMM studies for Venezuela. 5–7 For example, in 2019, 48.9% were classified as hypertensive, 6 which may be due in small part to an older average age of 2021 screenees (56.4 vs. 54.7 years). On the other hand, sampling of MMM campaigns is opportunistic and not randomized, and it is possible that hypertensive patients participated in higher numbers than in previous years after the restrictions from the COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, in the MMM 2017, 2018, and 2019 campaigns, a higher frequency of hypertension was reported as 48.9%, 48.4%, and 48.9%, among screened populations of mean age 53.2, 54.2, and 54.7 years, respectively. 5 , 6 , 7 …”
Section: Introductionmentioning
confidence: 99%
“… 19 The results of a similar campaign in 2017 in Venezuela indicated that 48.9% of the people had hypertension. 20 In this regard, the specialists of the World Heart Federation and the Lancet Commission on Hypertension believe that the main strategy to control hypertension around the world is people’s awareness about their blood pressure status and taking the measures to inform people about the blood pressure in different groups. 21 , 22 In general, the studies revealed that implementing campaigns and informing the public about controlling blood pressure and the importance of the complications caused by hypertension is an effective strategy for reducing the number of the diseases caused by hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Obesity was prevalent in 14.2% of participants and 4.8% were underweight in the present campaign comparing to 16.0% and 4.1%, respectively of individuals included in the MMM2017 campaign. 6 Carballo-Arias 7 reported important changes in the economy, job situation, and health in Venezuela since 2006 and a recent Lancet editorial described how the humanitarian, economical, and health crisis is deteriorating. 8 This may explain reductions in the prevalence of obesity in the Venezuelan population since obesity in the CARMELA study was reported in 25.1%.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, diabetes was present in 9.5% of individuals in contrast to 10.7% of cases reported last year. 6 …”
Section: Discussionmentioning
confidence: 99%